Paradoxical low-flow aortic stenosis is defined by increased ventricular hydraulic load and reduced longitudinal strain. Issue 2 (February 2017) - Holmes, Anthony A.; Taub, Cynthia C.; Garcia, Mario J.; Shan, Jian; Slovut, David P.
Abstract : Aims: Patients with paradoxical low-flow severe aortic stenosis (PLF-AS) reportedly have higher left ventricular hydraulic load and more systolic strain dysfunction than patients with normal-flow aortic stenosis. This study investigates the relationship of systolic loading and strain to PLF-AS to further define its pathophysiology. Methods: One hundred and twenty patients (age 79 ± 12 years, 37% men) with an indexed aortic valve area (AVAi) of 0.6 cm 2 /m 2 or less and an ejection fraction of 50% or higher were divided into two groups based on indexed stroke volume (SVi): PLF-AS, SVi ⩽ 35 ml/m 2, N  = 46; normal-flow aortic stenosis, SVi > 35 ml/m 2, N  = 74). Valvular and arterial load were assessed using multiple measurements, and strain was assessed using speckle-tracking echocardiography. Results: Patients with PLF-AS were found to have more valvular load (lower AVAi, P  = 0.028; lower energy loss coefficient, P  = 0.001), more arterial load [decreased arterial compliance and increased systemic vascular resistance (SVR), both P  < 0.001] and more total hydraulic load [increased valvuloarterial impedance (Zva), P  < 0.001]. Transvalvular gradients and arterial pressures were similar. Longitudinal strain was lower in PLF-AS ( P  < 0.001), but circumferential and rotation strains were similar. On adjusted regression, AVAi, SVR and longitudinal strain were associated with PLF-AS [odds ratio (OR) = 1.34, P  = 0.043; OR = 1.31, P  = 0.004; OR = 1.34, P  = 0.011, respectively]. When SVR and AVAi were replaced with Zva, longitudinal strain and Zva (OR = 1.38, P  = 0.015; OR = 1.33, P  < 0.001 for both, respectively) were associated with PLF-AS. Conclusion: Increased hydraulic load, from more severe valvular stenosis and increased vascular resistance, and longitudinal strain impairment are associated with PLF-AS and their interplay is likely fundamental to its pathophysiology. Abstract : Supplemental Digital Content is available in the text